VAR IPP-IPC Model Simulation - Juan P. Pérez Monsalve; Alfredo Trespalacios Carrasquilla (Cuadernos de Administración, 2014)
This work analyzed the relationship of the two main Price indicators in the Colombian economy, the IPP and the IPC. For this purpose, we identified the theory comprising both indexes to then develop a vector autoregressive model, which shows the reaction to shocks both in itself as in the other variable, whose impact continues propagating in the long term. Additionally, the work presents a simulation of the VAR model through the Monte Carlo method, verifying the coincidence in distributions of probability and volatility levels, as well as the existence correlation over time